Module Stabilizing of Biocarbon Based Electrochemical Capacitor - Syarif, Nirwan; Rohendi, Dedi; Sudarsono, Wulandari; Wong, Wai (http://dx.doi.org/10.31427/IJSTT.2019.2.1.5, 2019)
One of the disadvantages of the electrochemical capacitor (EC) or supercapacitor compared with batteries is its low specific energy. It limits of EC to meet the energy needs of the electrical-electronic devices, such as electric cars. To overcome those limitations, it needs a serial circuit to increase the voltage range, and parallel circuits to increase the storage capacity. Practically, the module that built from 2-6 pieces of 2.5V EC cells will not feasible to make the module with the voltage of 5-15 V. It was found that the voltage of the EC cell could decreases to about 2.0 V, so that the capacitance of the module significantly reduced. This paper reports the basic methods that can be applied to overcome these problems by using a stabilizing or balancing component. The balancing components used in this study were a resistor, a Zener diode, and a Schottky diode. Each component was attached to every EC cell. The influence of the Zener and Schottky diode was observed as a component of a blocking diode. The results showed that the use of a 100-ohm resistor and Zener diode reduces voltage peaks while the use of blocking diode modules leads to increased discharge time. In general, there was no significant change in the charging time, both with and without the balancing and blocking component.